1999
DOI: 10.1002/(sici)1097-0134(19990815)36:3<370::aid-prot11>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of substrate dephosphorylation in lowMr protein tyrosine phosphatase

Abstract: Substrate dephosphorylation by the low molecular weight protein tyrosine phospha-tases proceeds via nucleophilic substitution at the phosphorous atom yielding a cysteinyl phosphate intermediate. However, several questions regarding the exact reaction mechanism remain unanswered. Starting from the crystal structure of the enzyme we study the energetics of this reaction, using the empirical valence bond method in combination with molecular dynamics and free energy perturbation simulations. The free energy profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…In this work, we have studied the energetics of the second step of the reaction catalyzed by the low M r PTP (for review see [16,17]), using the empirical valence bond (EVB) method in combination with molecular dynamics (MD) and free energy perturbation (FEP) simulations [18,19]. The obtained reaction free energy pro¢le is combined with that of the ¢rst reaction step published by us elsewhere [20,21] and the calculated overall rate limiting barrier of 16 kcal/mol agrees well with the observed turn-over rate for the wild-type enzyme. An alternative reaction mechanism has been investigated for the mutant enzyme lacking the general acid/base (Asp-129 in low M r PTP) and the e¡ect of mutating Cys-17 is examined.…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…In this work, we have studied the energetics of the second step of the reaction catalyzed by the low M r PTP (for review see [16,17]), using the empirical valence bond (EVB) method in combination with molecular dynamics (MD) and free energy perturbation (FEP) simulations [18,19]. The obtained reaction free energy pro¢le is combined with that of the ¢rst reaction step published by us elsewhere [20,21] and the calculated overall rate limiting barrier of 16 kcal/mol agrees well with the observed turn-over rate for the wild-type enzyme. An alternative reaction mechanism has been investigated for the mutant enzyme lacking the general acid/base (Asp-129 in low M r PTP) and the e¡ect of mutating Cys-17 is examined.…”
Section: Introductionmentioning
confidence: 61%
“…It is clear that the characteristic signature motif corresponding to the phosphate binding loop is the key catalytic factor in these enzymes. It appears to be optimized for stabilizing a double negative charge in the center of the loop (it was earlier shown that the enzyme cannot accommodate a total charge of 33 [21]). This explains both the e¤cient stabilization of the transition states and why sig-ni¢cant accumulation of the reaction intermediate does not occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The improbability of binding a dianion, as opposed to a monoanion, in the active site carrying an ionised nucleophile was further shown by Kolmodin et al using binding free energy calculations [34]. They also reproduced the energetics of the whole reaction pathway for both the wild type and D128A mutant LMPTP using a monoanionic substrate [29].…”
Section: Ionisation State Of the Substratementioning
confidence: 92%